Basic Dual-Arm Manipulator Kinematics Using Forward Kinematics Method and Aided by Autodesk Inventor - Asmara Yanto (Jurnal Teknik Mesin (JTM), 2018)
This work aims to simulate the kinematics of a basic dual-arm manipulator by using the forward kinematics method and aided by the Autodesk Inventor software. Dual-arm manipulator consists of 7 joints and 6 links. One base link, one shoulder link, two right arm links and two left arm links. Each link is designed with the following length: 310 mm length of link base, 580 mm length of shoulder link, 280 mm length of the first right arm link and left arm link, 222 mm length of the second right arm link and left arm link. The degree of freedom of the dual-arm manipulator is five rotations (5R), namely R1 for base link and shoulder link, R2 for the first left arm link, R3 for the second left arm link, R4 for the first right arm link and R5 for the second right arm link. Parts and assembly of the dual-arm manipulator are designed with Autodesk Inventor. Dual-arm manipulator motions were simulated in two types of trajectory planning. From the simulation for both trajectory planning, the positions of ended left arm and right arm for each step of trajectory planning were visualized and defined.